Using Drosophila as a model insect. - Schneider, D. (Nature Reviews. Genetics, 2000)
The fruit fly Drosophila melanogaster has become such a popular model organism for studying human disease that it is often described as a little person with wings. This view has been strengthened with the sequencing of the Drosophila genome and the discovery that 60% of human disease genes have homologues in the fruit fly. In this review, I discuss the approach of using Drosophila not only as a model for metazoans in general but as a model insect in particular. Specifically, I discuss recent work on the use of Drosophila to study the transmission of disease by insect vectors and to investigate insecticide function and development.